ANALYSIS OF INCOME AND EFFICIENCY OF SHRIMP FLOSS PRODUCT INNOVATION AS AN EFFORT TO UTILIZATE SHRIMP RECEK WASTE IN AYAKH UGAN MSME’S - Windi Lestari; Doris Saputra; M. Aldoni; Antika Dedes Juleha; Ema Pusvita; Endang Lastinawati; Henny Rosmawati; Putri Ayu Ogari; Septianita; Citra Pratiwi Prayitno; Herdaning Putri (RADJA PUBLIKA, 2025)
This study aims to analyze the income and efficiency of the shrimp floss product innovation business based on shrimp waste at Ayakah Ugan MSMEs, Ogan Komering Ulu Regency. Shrimp waste, which has been considered to have no economic value and has the potential to pollute the environment, is processed into shredded shrimp as an effort to diversify products while reducing and utilizing waste. The method in this study is an experimental method with a case study approach, where researchers conducted a trial of shrimp floss production using shrimp waste as the raw material. Data were analyzed descriptively quantitatively by calculating production costs, revenues, income, operating profits and business efficiency using the revenue cost ratio (R/C ratio). The results of the analysis show that the shrimp floss processing innovation product has an R/C ratio of 2.68. This value indicates that this business is efficient and feasible to be developed because every expenditure of 1 rupiah can generate income of more than 1 rupiah. The average income per production is Rp. 626,777. Based on the results of the study, the shrimp floss processing innovation product business is proven to be financially feasible and has great potential for further development. This innovation not only provides financial benefits for MSMEs but also supports the principles of a circular economy by utilizing fishery waste into value-added products.